HAZARDOUS WASTE IMPORT BAN POLICY AND PROBLEMS - Teddy Prasetiawan (Widyariset, 2012)
Transboundary movements of hazardous waste become a hot topic nowadays. Its characteristics that areharmful to humans and the environment make this type of waste is rejected by all countries anywhere in the world,including Indonesia. This paper will explain briefly about the definition of hazardous waste, the background ofhazardous waste import ban policy, and problems in the implementation of the policy. This study applies qualitativeand descriptive method by using secondary data. There is a tendency by the developed industrial countriesfor making the poor and the developing countries as “a giant trash can” for the hazardous waste they produced.So far, Basel Convention which was organized in order to address these concerns by establishing a ban of transboundarymovements of hazardous waste, has not been able to produce a binding agreement for all countries.Indonesia, which implements hazardous waste import ban policy, not only needs to harmonize all the rules relatedto hazardous waste management, but also needs to improve the supervision of illegal traffic of hazardous waste.